Cooperation between ARID3A and p53 in the transcriptional activation of p21WAF1 in response to DNA damage - Lestari, Widya; Arief Ichwan, Solachuddin Jauhari (2013)

(untitled)
ARID3A/DRIL1/Bright is a family member of AT rich interaction domain (ARID) DNA-binding proteins that involve in diverse biological processes. We have reported that p53 activates ARID3A transcription, and ARID3A overexpression induced G1 arrest. However, a role of ARID3A in the p53 pathway remains unclear. Here, ‘we show that ARID3A cooperates with p53 to transcriptionally activate p21WAF1, a p53-target gene important for cell-cycle arrest. ARID3A bound to its binding sites in the p21WAF1 promoter in vivo and in vitro, and induced p21WAF1 transcription in U2OS cells expressing wild-type p53 but not Saos-2 cells lacking p53. Co-expression of ARID3A with p53 cooperates to activate p21WAF1 transcription and the stably transfected p21WAF1 promoter. Mutation of the ARID3A binding sites reduced the p21WAF1 promoter activity, and siRNA-based ARID3A knockdown suppressed transcription of p21WAF1 but not proapoptotic NOXA and PUMA in response to DNA damage. Furthermore, p53 knockdown decreased ARID3A transcription, and, conversely, ARID3A overexpression or knockdown resulted in an increase or decrease in p53 stability, respectively. These results indicate cooperative and interdependent roles for ARID3A and p53 in transcriptional activation of p21WAF1 in response to DNA damage.